2016
DOI: 10.2147/cia.s117202
|View full text |Cite
|
Sign up to set email alerts
|

Successful aging: considering non-biomedical constructs

Abstract: ObjectivesSuccessful aging continues to be applied in a variety of contexts and is defined using a number of different constructs. Although previous reviews highlight the multidimensionality of successful aging, a few have focused exclusively on non-biomedical factors, as was done here.MethodsThis scoping review searched Ovid Medline database for peer-reviewed English-language articles published between 2006 and 2015, offering a model of successful aging and involving research with older adults.ResultsSeventy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 60 publications
6
57
1
4
Order By: Relevance
“…In addition to these aging services practitioners' perspectives being reflected in the research literature to date, there is also a close alignment between their views and those of older adult participants in studies of healthy aging. For example, Phelan and colleagues found that over 90% of older Japanese-Americans and Whites participating in longitudinal studies believe the following dimensions of successful aging were most important: remaining in good health until close to death, being able to take care of oneself until close to the time of death, and remaining free of chronic disease (25,26). Taken together, these perspectives from older adults bear close resemblance to those cited by the community practitioners who participated in this study.…”
Section: Discussionsupporting
confidence: 54%
“…In addition to these aging services practitioners' perspectives being reflected in the research literature to date, there is also a close alignment between their views and those of older adult participants in studies of healthy aging. For example, Phelan and colleagues found that over 90% of older Japanese-Americans and Whites participating in longitudinal studies believe the following dimensions of successful aging were most important: remaining in good health until close to death, being able to take care of oneself until close to the time of death, and remaining free of chronic disease (25,26). Taken together, these perspectives from older adults bear close resemblance to those cited by the community practitioners who participated in this study.…”
Section: Discussionsupporting
confidence: 54%
“…assessed factors related to ageing and identified four aspects that are associated with successful ageing: (i) avoiding disease and disability; (ii) maintaining cognitive, mental and physical functions; (iii) actively engaging in life; and (iv) being psychologically well . Currently, the definition of healthy ageing remains unsettled due to differences in diagnostic criteria or depending on the research focus …”
Section: Introductionmentioning
confidence: 99%
“…The elderly population worldwide is growing rapidly and this demographic shift presents opportunities and challenges for society and health professionals to maximize functional capacity in this group (Beard & Bloom, ; World Health Organization, ). Along this line, the nursing care for the elderly requires a multidimensional assessment that includes physiological (functional), psychological (spiritual), and social aspects to diagnose their real needs and risk factors in order to implement interventions appropriately in each case and to promote successful aging (Carver & Buchanan, ; Martinson & Berridge, ; Morilla‐Herrera et al., ).…”
Section: Introductionmentioning
confidence: 99%